Language and face in interactions: emotion perception, social meanings, and communicative intentions - Liu, Mingya; Schwab, Juliane; Hess, Ursula (Frontiers in Psychology, 2023)
Introduction Human emotions can be complex to interpret as they have multiple sources and are often times ambiguous, for example, when the signals sent by different channels of communication are inconsistent. Our study investigates the interaction of linguistic and facial expressions of emotions. Methods In two experiments, participants read short scenarios in German containing a direct utterance with positive or negative emotive markers, in combination with different facial expressions as still images of the speaker (i.e., the protagonist in the story). They answered questions about their perception regarding the intensity of the emotions (e.g., happiness, sadness), the properties of the expresser (e.g., honesty, warmth, likeability) and their relation to the addressee (e.g., closeness), as well as the expresser intention (e.g., irony, joke). Results The findings suggest that facial expressions have a more dominant role in the emotion perception in comparison to emotive markers. Furthermore, consistent and inconsistent combinations of emotive markers and facial expressions convey distinct social meanings and communicative intentions. Conclusion This research points to the importance to consider emotive markers in the emotional context that they occur in.